(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The purpose of this article is to show an example of how a small metalworking company can make your product development more agile, flexible and value generating using Lean. Presents itself the generic product development process, the traditional development process in the industry of mechanical metal in the province of Misiones, the Toyota product development system and the new development system in the company studied, which contains a Lean approach and agility concepts. It begins with market research of customer demands in reference to needs, demands and value functions of the product, which will allow to transfer to the requirements of the organization and thus be able to achieve the satisfaction of customer needs and expectations. . In the next phase, the final requirements of the product components are defined and this is when the concept of agility intervenes, carrying out iterative processes that improve the customer’s requirements. It also allows a product adaptable to changes by subdividing it into small advances, working together with the client to achieve a flexible and improved design. Next, the data obtained in the first quality matrix (FVD) is used with the addition of the Lean approach, with which functions and technical characteristics that provide product value are prioritized.